A Chequered History of Governors' Discretionary Powers under Article 163. (September 2017) - Tiwari, Atul Kumar
This article examines how governors have made more use of their discretionary powers than the president. The reason is found in Article 163 of the Constitution that allows use of discretionary powers of the governors. Despite being antithetical to the responsible governments in the states, such powers were assigned to the governors after contentious debates in the Constituent Assembly in order to retain a strong centre in the aftermath of unification of India. This article recommends that there is a need for some reforms particularly with regard to appointment and tenure of the governors that aid and abet the constitutional transgression by the governors. It also holds that codification of a body of conventions would further bring the actions of the governors within the accepted canons of interpretation of the Constitution.